Self-assembly in elastin-like recombinamers: a mechanism to mimic natural complexity. (March 2019) - Quintanilla-Sierra, L.; García-Arévalo, C.; Rodriguez-Cabello, J.C.
Abstract: The topic of self-assembled structures based on elastin-like recombinamers (ELRs, i.e., elastin-like polymers recombinantly bio-produced) has released a noticeable amount of references in the last few years. Most of them are intended for biomedical applications. In this review, a complete revision of the bibliography is carried out. Initially, the self-assembly (SA) concept is considered from a general point of view, and then ELRs are described and characterized based on their intrinsic disorder. A classification of the different self-assembled ELR-based structures is proposed based on their morphologies, paying special attention to their tentative modeling. The impact of the mechanism of SA on these biomaterials is analyzed. Finally, the implications of ELR SA in biological systems are considered. Graphical abstract: Image 1